How capitalism failed the Arab world the economic roots and precarious future of Middle East uprisings - Heydarian, Richard Javad (Economic controversies, 2014)
Economic liberalization has failed in the Arab world. In 'How Capitalism Failed the Arab World', Richard Heydarian shows how years of economic mismanagement, political autocracy and corruption have encouraged people to revolt, and how the initial optimism of the uprisings is now giving way to bitter power struggles, increasing uncertainty and continued economic stagnation.